Implementation of ARKA Model (Aktivitas, Refleksi, Konseptualisasi, Aplikasi) in PAI Learning: Building 21st Century Competencies - Ilyasa, Faisal Fauzan; Rahardja, Muhammad Nurfaizi Arya; Firmansyah, Mokh. Iman; Faqihuddin, Achmad; Muflih, Abdillah (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
Learning models play a vital role in supporting the achievement of learning objectives as conceptual frameworks that describe systematic procedures and guide designers.  This study aims to describe the ARKA Model (Aktivitas, Refleksi, Konseptualisasi, Aplikasi) in PAI learning at SMA Negeri Bandung through learning system theory, including planning, implementation, and evaluation. This research uses a qualitative approach and case study method with data collection techniques through observation, interviews, and documentation, which are then analyzed through the reduction stage. This research found three essential things: (1) planning the use of the ARKA model in PAI learning consists of preparing lesson plans, which include objectives, materials, methods, media, and teaching resources. The curriculum used is the 2013 national curriculum. (2) The implementation of PAI learning using the ARKA model consists of four stages adapted to the syntax of this ARKA model: Activity, Reflection, Conceptualization, and Application. These four steps have been included in the core activities. (3) The evaluation of PAI learning using the ARKA model is divided into formative and summative evaluation. The evaluation results of the ARKA learning model in PAI learning positively impact students in improving their ability to think critically, communicate well, collaborate, and be creative.